Mass transport and charge transfer through an electrified interface between metallic lithium and solid-state electrolytes - Katzenmeier, Leon; Gößwein, Manuel; Carstensen, Leif; Sterzinger, Johannes; Ederer, Michael; Müller-Buschbaum, Peter; Gagliardi, Alessio; Bandarenka, Aliaksandr S. (Communications chemistry, 2023)
All-solid-state Li-ion batteries are one of the most promising energy storage devices for future automotive applications as high energy density metallic Li anodes can be safely used. However, introducing solid-state electrolytes needs a better understanding of the forming electrified electrode/electrolyte interface to facilitate the charge and mass transport through it and design ever-high-performance batteries. This study investigates the interface between metallic lithium and solid-state electrolytes. Using spectroscopic ellipsometry, we detected the formation of the space charge depletion layers even in the presence of metallic Li. That is counterintuitive and has been a subject of intense debate in recent years. Using impedance measurements, we obtain key parameters characterizing these layers and, with the help of kinetic Monte Carlo simulations, construct a comprehensive model of the systems to gain insights into the mass transport and the underlying mechanisms of charge accumulation, which is crucial for developing high-performance solid-state batteries. All-solid-state lithium-ion batteries are promising energy storage devices owing to their safe use and high energy density, whereby understanding electrode and solid electrolyte interfaces is key for battery development. Here, the authors use spectroscopic ellipsometry, impedance measurements, as well as Monte Carlo simulations to elucidate the formation of charge depletion layers at the electrode/electrolyte interface.